KESELARASAN ANTARA KURIKULUM DAN PEMBELAJARAN IPA-KIMIA SMP - oktariani oktariani; andhika baruri (UIR Press, 2019)
ABSTRACT This study was conducted to: (1) analyze the level of alignment between curriculum and science-chemistry learning in Junior High School and (2) describe the discrepancies between curriculum and science-chemistry learning in Junior High School in term of cognitive demands as well as subject content covered. This study was descriptive research which combined survey method and content analysis. The survey was conducted on 25 Junior High School science teacher in Bandung. Content analysis conducted on curriculum science-chemistry document. To determine the degree of alignment criteria, this study used the method developed by Porter. The results showed that alignment index between chemistry content on TIMSS and science-chemistry learning in Junior High School was 0.572 (middle level). This imperfect of alignment is characterized by the discrepancies in term of subject content covered and cognitive demands. This can affect certainly toward the achievement of students and quality of education in Indonesia. Keywords: Alignment Index, alignment, curriculum, science-chemistry learning in Junior High School,. ABSTRAK Penelitian ini dilakukan untuk: (1) menganalisis keselarasan antara kurikulum dan pembelajaran IPA-Kimia SMP, dan (2) mendeskripsikan perbedaan cakupan materi dan tuntutan kemampuan kognitif antara kurikulum dan Pembelajaran IPA-Kimia SMP. Penelitian ini merupakan penelitian deskriptif yang menggabungkan metode survei dan analisis konten. Survei dilakukan terhadap 25 orang guru IPA SMP di kota Bandung. Penentuan subjek penelitian ini dilakukan dengan teknik stratified sampling. Analisis konten dilakukan terhadap kurikulum IPA-Kimia SMP. Untuk menentukan kriteria tingkat keselarasan, metode yang digunakan adalah metode yang dikembangkan oleh Porter. Hasil penelitian menunjukkan bahwa indeks keselarasan antara kurikulum dengan pembelajaran IPA-Kimia SMP sebesar 0,572 (tingkat sedang). ketidaksempurnaan tingkat keselarasan ini ditandai dengan adanya perbedaan cakupan materi dan tuntutan kemampuan kognitif. Ini tentu mempengaruhi pencapaian siswa dan mutu Pendidikan di Indonesia Kata-kata kunci: indeks keselarasan, keselarasan, kurikulum, pembelajaran IPA-Kimia SMP